DIFFERENCES IN FLOW RATE AND SALIVA PH IN USERS AND NON-USERS OF FIXED ORTHODONTIC APPLIANCES - Viona Sekar Melati; Ernawati; Ageng Wicaksono (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Fixed orthodontic treatment is a type of dental treatment that is very popular throughout the world, not only to improve function but also lifestyle. However, it has an impact on the condition of the oral cavity, namely the flow rate and pH of salivary, which can affect dental and oral health. This study aims to determine the differences in flow rate and saliva pH between users and non-users of fixed orthodontic devices. Materials and Methods: This type of research is analytical observational, with a cross sectional approach. The population in this study were students class 2020, 2021, and 2022, the sample in this study was 116 students. Data collection by observation, interviews and examination. The method for measuring saliva flow rate with drainase and saliva pH using the Hanna HI98107 pH meter. Univariate and bivariate data analysis (independent sample t test). Results and Discussions: The results of the study showed that the there was a difference in saliva flow rate in users and non-users of fixed orthodontic appliances (p-value 0.001), there is a difference in saliva pH between users and non-users (p-value 0.000). Conclusion: The use of fixed orthodontic can affect saliva flow rate and salivary pH.